The Effect of Workload and Stress Through Work Motivation on Employee Performance in the Student Affairs Sector at Surabaya State University - Febrianti, Nur Ismi; Witjaksono, Andre Dwijanto; Surjanti, Jun (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This work was prepared to analyze the influence of workload, work stress, and work motivation on the performance of students and alums employees of the State University of Surabaya (UNESA) who have PTNBH status. The methodology used was a quantitative Expost Facto approach using ordinal data analysis through Somer's D analysis with the SPSS version 16 application. The initial steps included conducting validity and reliability tests to ensure the data integrity of 24 student-employee respondents at Surabaya State University. The research results reveal a relationship between work stress and the motivation of student affairs employees at Unesa. Second, there is a relationship between workload and the motivation of student affairs employees at Unesa. Third, there is a relationship between work stress and the performance of student affairs employees at Unesa. Fourth, there is a relationship between workload and the performance of student affairs employees at Unesa. Fifth, there is a connection between work motivation and the performance of student affairs employees at Unesa.